Role of Enterprise Resource Planning and Total Quality Management in Supply Chain Organizational Performance - Setyadi, Antonius (International Journal of Supply Chain Management, 2019)
The objective of this study is to examine the effect of enterprise resource planning (ERP) and total quality management (TQM) on supply chain organizational performance in Indonesia. Therefore, the current study focused on supply chain companies in Indonesia. Additionally, the current study introduced mediating variable, namely; supply chain organizational excellence. The employees of Indonesian supply chain companies having direct involvement in supply chain activities were considered to collect the data. Thus, total two hundred questionnaires were sent to Indonesian supply chain companies by using mail survey. This study used SPSS for preliminary analysis and PLS to examine the relationship between variables. Results of the study highlighted that ERP and TQM has key role to promote supply chain organizational performance with the help of supply chain organizational excellence. It is found that supply chain organizational excellence helps to transfer the positive effect of ERP and TQM on supply chain organizational performance. Therefore, Indonesian companies should focus on supply chain organization excellence.